Sosialisasi Perilaku Kerja Inovatif bagi Para Pelaku Usaha di Desa Kertayasa, Kuningan - Arraniri, Iqbal; Rois, Tatang; Prayudi, Deri (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Community service in the form of socialization of innovative work behavior, aims to encourage business actors to be open to changes and developments in market trends, The method of implementing community service activities is using the Participatory Rural Appraisal Method which consists of four stages: preparation stage, FGD stage, documentation and analysis, and follow-up. The Priority ranking table explains the priority in utilizing digital technology for business development. Understanding the concept of innovative work behavior in the business world can help raise awareness of the importance of creativity and adaptation in increasing business competitiveness. The entrepreneurial gap in rural areas, especially in Kertayasa Village, Sindangagung District, Kuningan Regency, can be minimized by focusing on optimizing digital marketing training based on economic impact, ease of implementation, sustainability, and availability of resources, as a manifestation of innovative work behavior that provides direct and indirect benefits for MSME actors, starting from the emergence of ideas to the implementation of these ideas with a commitment from all parties involved for mutual success.